Pengaruh Small Sided Games dan Passing Support dalam Meningkatkan Keterampilan Passing Atlet Futsal Klub Venus Semarang - Yogi Ferdy Irawan; Serli Oktavia Puspita Sari (Mathematics Education Study Program, 2025)
Many futsal athletes still have difficulty in applying basic techniques during matches, especially passing techniques. In fact, passing is a fundamental skill that must be mastered in futsal. Considering that the Venus FC Semarang Club will soon compete in the AFP U19 Championship Central Java match, a more innovative training method is needed. This study aims to evaluate the effectiveness of small-sided games and passing support training in improving the passing skills of Venus FC Semarang Club athletes. This study used an experimental design with a two-group pretest-posttest design model. The sample used was 16 athletes. Data analysis was carried out using normality and homogeneity tests to meet data requirements, and the t-test was used to test the hypothesis. The results of the t-test showed that small-sided games training had a Sig. (2-tailed) value of 0.01 <0.05, while passing support training had a Sig. (2-tailed) value of 0.000 <0.05. In addition, the difference test results showed that small-sided games training improved passing skills by 43.18%, while passing support training improved passing skills by 21.8%.